Synthesis and properties of GuNA purine/pyrimidine nucleosides and oligonucleotides. Issue 46 (12th November 2020) - Kumagai, Shinji; Sawamoto, Hiroaki; Takegawa-Araki, Tomo; Arai, Yuuki; Yamakoshi, Shuhei; Yamada, Katsuya; Ohta, Tetsuya; Kawanishi, Eiji; Horie, Naohiro; Yamaguchi, Takao; Obika, Satoshi
Abstract : Facile synthesis of GuNA (guanidine-bridged nucleic acid) phosphoramidites bearing thymine, adenine, guanine, and 5-methylcytosine nucleobases and a robust method for the preparation of GuNA-modified oligonucleotides are described. Abstract : We recently designed guanidine-bridged nucleic acids (GuNA), and GuNA bearing a thymine (T) nucleobase was synthesized and successfully incorporated into oligonucleotides. The GuNA-T-modified oligonucleotides possessed high duplex-forming ability towards their complementary single-stranded RNAs and were highly stable against 3′-exonuclease. Therefore, GuNA is a promissing artificial nucleic acid for therapeutic antisense oligonucleotides. We herein report the facile synthesis of GuNA phosphoramidites bearing adenine (A), guanine (G), and 5-methylcytosine ( m C) nucleobases and a robust method for the preparation of GuNA-modified oligonucleotides, even with sequences having acid-sensitive purine nucleobases. Oligonucleotides modified with GuNA-A, -G, or - m C possessed high duplex-forming ability, similar to those modified with GuNA-T. Moreover, some of the GuNA-modified oligonucleotides were revealed to have high base discriminating ability compared with that of their natural counterparts. GuNA nucleosides exhibited no genotoxicity in bacterial reverse mutation assays. Thus, all GuNAs (GuNA-T, -A, -G, and - m C) are now available to be examined in therapeutic applications.